2007
DOI: 10.1080/09658210601055750
|View full text |Cite
|
Sign up to set email alerts
|

Semantic self-knowledge and episodic self-knowledge: Independent or interrelated representations?

Abstract: In this study of the structure of self-knowledge, we examined priming effects for the recall of personal episodes in order to investigate whether abstract trait knowledge and personal episodes are independent mental representations. We found that accessing similar abstract representations of traits facilitated a faster recall of related personal episodes than did accessing irrelevant abstract representations of traits (Experiments 1 and 2), reading a nonword prime (Experiments 2 and 3), accessing knowledge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 39 publications
2
24
1
1
Order By: Relevance
“…SCC was not associated with enhanced episodic recall, in contrast to prior research indicating that individuals with high SCC may have more stable semantic self-knowledge structures in which to support episodic memories (Conway 2001;Dunkel and Lavoie 2005;Neimeyer and Rareshide 1991;Sakaki 2007). These results may reflect the tendency of individuals with high Bold values indicate significance at the .05 or .01 level SCC to engage in more ''meaning-making'' during autobiographical recall, which is theorized to be an important process in integrating AMs into patterns and consolidating the self (Singer et al 2007).…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…SCC was not associated with enhanced episodic recall, in contrast to prior research indicating that individuals with high SCC may have more stable semantic self-knowledge structures in which to support episodic memories (Conway 2001;Dunkel and Lavoie 2005;Neimeyer and Rareshide 1991;Sakaki 2007). These results may reflect the tendency of individuals with high Bold values indicate significance at the .05 or .01 level SCC to engage in more ''meaning-making'' during autobiographical recall, which is theorized to be an important process in integrating AMs into patterns and consolidating the self (Singer et al 2007).…”
Section: Discussioncontrasting
confidence: 86%
“…In a study using Marcia's (1966) 4 levels of identity formation (i.e., diffuse, moratorium, foreclosed, and achieved), emerging adults with more committed identity statuses (i.e., achieved and foreclosed) were found to recall a greater number of AMs during a cued recall task, suggesting that individuals with more stable identities may have more articulated semantic self-knowledge structures to support episodic memories (Neimeyer and Rareshide 1991). In line with this conclusion, recent evidence indicates that episodic and semantic components of AM are structurally related, such that accessing semantic self-knowledge facilitates access to episodic memories (Sakaki 2007). This evidence is in keeping with the Self-Memory System (SMS) model proposed by Conway and Pleydell-Pearce (2000), which assumes that abstract knowledge about the self is linked with episodic knowledge.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In agreement with this view, it has been shown that CMS activity increased in a linear fashion with increasing self-relevance . When reflecting on their own psychological characteristics, people can generate different mental models of themselves for different time periods (by retrieving relevant knowledge from semantic and/or episodic memory; Klein et al, 2002;Conway, 2005;Sakaki, 2007), and CMS might index the degree to which a particular mental model refers to the present self. In other words, CMS might sustain the process of identifying oneself with the current mental model of the self (which is therefore regarded as 'me') vs distancing oneself from representations of past selves (which are therefore considered as 'not-me' anymore; see James, 1890, for an early account of the process of 'appropriating' vs 'rejecting' particular mental contents as part of oneself).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, Sakaki (2007) proposed that Klein and Loftus's conclusion that semantic and episodic trait self-knowledge are functionally independent (e.g., Klein, Babey, & Sherman, 1997;Klein & Loftus, 1993a;Klein, Loftus, Trafton, & Fuhrman, 1992b) was based on questionable assumptions and not supported by the available evidence. In this paper we show that Sakaki (2007) has misinterpreted our position on the independence of self-knowledge, omitted mention of large portions of the relevant research at odds with her contention, and conducted her studies with procedures we explicitly warned against due to interpretive ambiguities associated with their use.…”
mentioning
confidence: 97%